Analisis Disparitas Harga dan Korelasi terhadap Dana Desa: Studi Kasus Bawang Merah dan Cabai Merah: Institut Pertanian Bogor - Dian Verawati Panjaitan; Tanti Novianti; Muhammad Fazri; Sri Retno Wahyu Nugraheni (IPB University, 2019)
Price disparity is a crucial issue for Indonesia due to transportation cost and production cost. The prices of chili and shallot are rellatively fluctuating between times and between regions. Both of them have an important role to consume and use in both food and non-food industries. The government has implemented several policies to reduce price disparity between regions such as sea toll and infrastructure: rood, bridge, and irrigation systems which used village funds. This study examines the impact of village funds to the price disparity in chili and shallot market at provincial lavel. The findings show that price disparities between provinces still occur, especially in the eastern and western regions. Papua is a province with the highest prices in both commodities. The study also found no correlation between the village funds and the price of chili and shallot.